Pengaruh Pemberian Tens Dan Myofascial Release Terhadap Penurunan Nyeri Leher Mekanik - Pajar Haryatno; Heru Purbo Kuntono (Poltekkes Kemenkes Surakarta, 2016)
Abstract: The pain, TENS, Myofascial Release. The research objective was to determine the effect of administration of TENS and Myofascial Release to decline Mechanical Neck Pain. This study design is one group of pre and post-test design. Subjects and treatment are 20 people who suffer from neck pain mechanic who met the study criteria given TENS and myofascial release treatment for 2 weeks. Points clinical research